Multifunctional Organic Vertical Photodiodes for Photo‐Detection and Photo‐Synapse Enabled by Modulation of the Interface Energy Barrier. Issue 21 (7th August 2022) - Liu, Tianhua; Lin, Qijie; Ma, Yao; Wang, Song; Chen, Hao; Wei, Yanan; Song, Yu; Shen, Liang; Huang, Fei; Huang, Hui
Abstract: Multifunctional organic optoelectronic devices are of great significance for the development of low‐energy consumption and space‐constrained systems. Herein, multifunctional organic photodiodes integrating transient light detection and photo‐synaptic functions in one device are unprecedentedly achieved upon readily changing the direction of the external bias. Under negative bias, the devices exhibit excellent photodetection performance with high shot‐noise‐limited specific detectivity ( D s h ∗ \[D_{sh}^*\]  > 10 13 Jones) in the range from ultraviolet, visible, to near infrared and large linear dynamic range (188 dB at 915 nm), which are among the best organic photodetectors. Interestingly, the photodiode devices change to work as organic photosynapses upon tuning the external bias to be positive. Associative learning behavior is successfully simulated in an all‐optical way, while high image recognition accuracy (>80%) is realized based on artificial neural network. The mechanism studies reveal that the interface energy barrier is critical for achieving the multi‐function in one device. Finally, the universality of electrically switchable transient light detection and photo‐synaptic functions is further studied. This work provides a novel method for constructing vertical diode‐type organic optical synapses and developing multifunctional organic electronics. Abstract : Multifunctional organic photodiodes based on the organic bulk‐heterojunction active layer are fabricated. Transient light detection and photo‐synaptic functions are unprecedentedly achieved upon simply changing the direction of the external bias. The devices show high detectivity and large linear dynamic range as photodetectors, and low energy consumption and linear conduction state update as photo‐synaptic devices.